Synthesis and characterization of ZnO-decorated GO nanocomposite material with different ZnO loading through sol-gel method - Nurul ‘Adilah Rosnan; Teow, Yeit Haan; Abdul Wahab Mohammad; Hamad Khalifa (Penerbit Universiti Kebangsaan Malaysia, 2018)
This work aimed is to synthesis a well dispersed zinc oxide (ZnO) nanoparticles (NPs) decorated on graphene oxide (GO) nanosheet with a practical way by using sol-gel technique. Zinc acetate dehydrate (Zn(CH3COO) 2·2H2O) was used as precursor of ZnO and absolute ethanol as solvent. 1 weight percent (wt%), 5 wt%, 10 wt%, and 20 wt% of ZnO was decorated on GO nanosheet. A series of analysis was carried out to characterize the synthesized ZnO-decorated GO nanocomposite material. The results of XRD analysis show some long area of peak at 25° to 80° allocate for ZnO in the ZnO-decorated GO nanocomposite material. By performing zeta potential analysis, the findings show that there was increment of negative surface charge on ZnO-decorated GO nanocomposite material. The experiment result also found that the hydrodynamic particle size of ZnO-decorated GO nanocomposite material become larger when high ZnO loaded. FESEM micrographs demonstrated that spherical-shaped of ZnO NPs appeared on the GO nanosheet with further proved by EDX where the content of ZnO-decorated GO nanocomposite material was composed by 71.3 wt% of C, 17 wt% of O, and additional element of 11.7 wt% of Zn. Thus, it can summarize that the synthesized ZnO-decorated GO nanocomposite material was high in purity. The findings in this study proved that ZnO NPs loading in ZnO-decorated GO nanocomposite material were successfully synthesized by sol-gel method. A ZnO-decorated GO nanocomposite material with layering ZnO NPs on GO nanosheet was produced.